2018
DOI: 10.1002/wrna.1471
|View full text |Cite
|
Sign up to set email alerts
|

Cytoplasmic functions of long noncoding RNAs

Abstract: Long noncoding RNAs (lncRNAs) are transcripts longer than 200 nucleotides found throughout the cell that lack protein-coding function. Their functions are closely linked to their interaction with RNA-binding proteins (RBPs) and nucleic acids. Nuclear lncRNAs have been studied extensively, revealing complexes with structural and regulatory roles that enable gene organization and control transcription. Cytoplasmic lncRNAs are less well understood, but accumulating evidence indicates that they also form complexes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
267
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 342 publications
(281 citation statements)
references
References 142 publications
7
267
0
1
Order By: Relevance
“…Subsequently, the expression status of HOXD-AS1 in HCC was validated employing 20 pairs of HCC and adjacent nonneoplastic tissues, as well as eight HCC cell lines (Bel-7402, Bel-7404, HepG2, Hep3B, SMMC-7721, MHCC97H, MHCC97L, and HCCLM3) and the normal human hepatic cell line L-O2 cells by qRT-PCR. 16 Thus, the subcellular localization of lncRNAs can provide clues to exploring the function of lncRNAs. A great deal of studies have shown that the functional mechanism of lncRNAs highly relies on their distinct subcellular localization.…”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, the expression status of HOXD-AS1 in HCC was validated employing 20 pairs of HCC and adjacent nonneoplastic tissues, as well as eight HCC cell lines (Bel-7402, Bel-7404, HepG2, Hep3B, SMMC-7721, MHCC97H, MHCC97L, and HCCLM3) and the normal human hepatic cell line L-O2 cells by qRT-PCR. 16 Thus, the subcellular localization of lncRNAs can provide clues to exploring the function of lncRNAs. A great deal of studies have shown that the functional mechanism of lncRNAs highly relies on their distinct subcellular localization.…”
Section: Resultsmentioning
confidence: 99%
“…Web servers can assist in quickly assessing experimentally determined or predictive RNA-RNA interactions [204] or even RNA-protein interactions [205,206]. Depending on the subcellular or extracellular compartmental localization of a lncRNA, this patterning will elude to the regulatory role of the gene, as well as how a lncRNA might execute its function [207][208][209]. Some LncRNAs that are localized to the nucleus or chromatin have been experimentally shown to function in cis to regulate the transcriptional expression of a neighboring gene, or in trans to regulate the transcriptional regulation of a subclass of genes through the interactions between heterogeneous nuclear ribonucleoproteins (hnRNPs) [42,54,60,210].…”
Section: Subcellular Localization and Binding Partnersmentioning
confidence: 99%
“…Among the important lncRNAs deregulated in cancer, ANRIL (antisense noncoding RNA in the INK4 locus) has been reported to recruit PRC2 and PRC1 complexes and repress gene expression . Post‐transcriptionally, lncRNAs are involved in every step of RNA metabolism, such as splicing, nuclear export, localization and mRNA decay, as well as protein translation and stability . In the cytoplasm, lncRNAs may work as decoys, by sequestering proteins from their usual targets.…”
Section: Introductionmentioning
confidence: 99%